Nanoscopic photoluminescence memory as a fingerprint of complexity in self-assembled alkyl/siloxane hybrids - Carlos, Luis D.; Bermudez, Veronica de Zea; Amaral, Vitor S.; Nunes, Silvia C.; Silva, Nuno J. O.; Ferreira, Rute A. Sa; Rocha, Joao; Santilli, Celso Valentim [UNESP]; Ostrovskii, Denis (Wiley-Blackwell, 2007)
A thermally activated photoluminescence memory effect, induced by a reversible order-disorder phase transition of the alkyl chains, is reported for highly organized bilayer alkyl/siloxane hybrids (see figure; left at room temperature, right at 120 degrees C). The emission energy is sensitive to the annihilation/formation of the hydrogen-bonded amide-amide array displaying a unique nanoscopic sensitivity (ca. 150 nm).